Effect of Permeant Cryoprotectants on Membrane Skeleton of Erythrocytes - Ivanov, Ivan T.; Paarvanova, Boyana K. (Problems of Cryobiology and Cryomedicine, 2019)
The impact of formamide (FA), N-methylformamide (MFA), N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) on the spectrin-based membrane skeleton of human erythrocytes was studied by thermal dielectroscopy. Upon heating the erythrocyte suspension, spectrin denatures at 49.5Â°C causing suspension impedance to change by Î”Z* = Î”Z’ + jÎ”Z". The - Î”Z" vs Î”Z’ plot reveals two dielectric relaxations on spectrin, called beta (0.05-1.0 MHz) and gamma (1.0-10 MHz) relaxations. At concentrations up to 5 M (relevant to cryoprotection) DMF and DMSO specifically subdued gamma-relaxation, while FA and MFA specifically inhibited beta-relaxation. Each effect was eliminated by preliminary washing of cryoprotectant and presumably did not depend on the osmotic pressure produced. Applied in combination, DMSO and FA neutralized their effects. Based on previous study, the results indicate that tested cryoprotectants detached the membrane skeleton from the lipid membrane, thereby compromising cell integrity. Â Probl Cryobiol Cryomed 2019; 29(3):Â 237â€“245.